2007
DOI: 10.1128/jvi.01057-07
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Stomatitis Virus mRNA Capping Machinery Requires Specific cis -Acting Signals in the RNA

Abstract: Many viruses of eukaryotes that use mRNA cap-dependent translation strategies have evolved alternate mechanisms to generate the mRNA cap compared to their hosts. The most divergent of these mechanisms are those used by nonsegmented negative-sense (NNS) RNA viruses, which evolved a capping enzyme that transfers RNA onto GDP, rather than GMP onto the 5 end of the RNA. Working with vesicular stomatitis virus (VSV), a prototype of the NNS RNA viruses, we show that mRNA cap formation is further distinct, requiring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…7B, lanes 10 and 11). This is consistent with the reported sequence-specific requirement for cap formation (29,42). Using this assay, we examined whether polymerases with defects in processivity as well as cap formation were able to cap in trans.…”
Section: Cap-defective L Proteins Generate Transcripts With 5 Triphossupporting
confidence: 65%
See 1 more Smart Citation
“…7B, lanes 10 and 11). This is consistent with the reported sequence-specific requirement for cap formation (29,42). Using this assay, we examined whether polymerases with defects in processivity as well as cap formation were able to cap in trans.…”
Section: Cap-defective L Proteins Generate Transcripts With 5 Triphossupporting
confidence: 65%
“…These data suggest a model for RNA synthesis in which addition of the mRNA cap plays a key role in controlling polymerase processivity. Coupled with the fact that the mRNA capping machinery requires specific signals in the RNA (29,42) and that mRNA cap methylation is accomplished by two activities that share a common SAM binding site (22), these data also show that the entire capping apparatus of these viruses is distinct to that employed by other systems. Furthermore, these experiments define a motif, GxxT[n]HR, that is essential for VSV mRNA cap formation.…”
Section: Discussionmentioning
confidence: 84%
“…A plausible explanation for this is that this single nucleotide change could have facilitated capping of some of the RNA initiated at ϩ3. In the case of VSV, it has been shown that initiation of RNA synthesis and capping of the nascent transcript are both directed by the GS signal (11,12). In addition, it has been shown that capping of VSV mRNA occurs when the transcript reaches 31 nt in length (36).…”
Section: Discussionmentioning
confidence: 99%
“…They are highly conserved in RSV, with 9 of 10 GS sequences being identical and the tenth having only slight differences (9). In related viruses, the GS signals have been shown to be multifunctional, directing the RdRp to cap and methylate the nascent transcript (10)(11)(12). Capping is thought to allow the RdRp to enter into a stable elongation mode in which it can extend the RNA to the GE signal, where the RdRp polyadenylates and then releases the mRNA (13).…”
mentioning
confidence: 99%
“…RTPase activity of L protein, the first step in viral mRNA capping, was tested in vitro using synthetic c-32 P-labelled RNA substrate containing sequences corresponding to viral genes. Viral mRNA 59 cis sequences were used as the substrate because in many negative-sense RNA viruses, the capping machinery of these viruses requires specific cis-acting signals in the RNA (Ogino et al, 2005;Ogino & Banerjee, 2007;Wang et al, 2007). Under optimal conditions, L protein in the RNP complex, as well as L protein co-expressed with P protein in insect cells, efficiently catalyses the removal of cphosphate from the triphosphate-ended RNA (Fig.…”
Section: Discussionmentioning
confidence: 99%